2014
DOI: 10.1590/0034-7167.2014670408
|View full text |Cite
|
Sign up to set email alerts
|

Adesão de pacientes hipertensos ao tratamento medicamentoso

Abstract: This is a descriptive, cross-sectional study, conducted in a center of Hypertension and Metabolism, which aimed to identify adherence to drug therapy in hypertensive patients, and to identify the factors, directly related to the patient, associated with this adherence. The sample consisted of 77 patients and the instrument used to verify patient compliance was the Measure of Adherence to Treatment and a semi-structured questionnaire consisting of factors for non-adherence to drug treatment. The results showed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
1
31

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(43 citation statements)
references
References 13 publications
2
7
1
31
Order By: Relevance
“…The study by Bezerra et al showed that 87% of patients had satisfactory medication adherence (21). In another study by Sweileh et al on 405 patients with diabetes in Nablus, Palestine, approximately 57.3% of the participants were considered adherent (22).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The study by Bezerra et al showed that 87% of patients had satisfactory medication adherence (21). In another study by Sweileh et al on 405 patients with diabetes in Nablus, Palestine, approximately 57.3% of the participants were considered adherent (22).…”
Section: Discussionmentioning
confidence: 98%
“…There are many studies on adherence to treatment regimen in the world (18)(19)(20)(21)(22)(23)(24), but there are few studies in this field in Iran and due to the financial burden of chronic diseases on the health and quality of life of the elderly, conducting more studies in this regard seems essential. Most of the studies examined medication adherence of patients with a certain disease, particularly diabetes; for the first time in Iran, researchers aimed at studying medication adherence of elderly people with several types of chronic diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Os participantes apontam, em seus discursos, o que a literatura já discutiu com bastante rigor e ratificam a compreensão de que o principal aspecto para a não identificação da doença hipertensiva está na assintomatologia. 15,16 Revelam também que, na maioria dos casos, a pessoa obtém o diagnóstico a partir de algum procedimento que precisou realizar ou, ainda, de uma consulta que estava agendada para outro problema e que, por acaso, o profissional aferiu a pressão arterial e, nesse momento, percebeu que esta se encontrava alterada.…”
Section: Desafios No Diagnóstico Da Hipertensão Arterial E Do Diabeteunclassified
“…Melo e colaboradores 28 destacam que exames laboratoriais básicos são importantes para a investigação clínica dos riscos cardiovasculares, bem como a mensuração da magnitude desses riscos.…”
Section: 28unclassified
“…Esta dificuldade pode estar relacionada com a baixa adesão ao tratamento medicamentoso para a hipertensão. 28 Um estudo transversal evidenciou que a prevalência do acesso a medicamentos de uso contínuo é maior na região Sul do que na região Nordeste. 29 Este trabalho apresenta algumas limitações.…”
Section: 28unclassified